The Association Of Adolescent Pregnancy With Stunting Incidence In Child Under Five Years Old; Literatur Review - Adelbertha A. B; Namita Candra Devi; Rita Oktavia Harahap; Astika Gita Ningrum (Jurnal sosial dan sains, 2022)
Background: Nowadays early marriage is a worldwide issue and influences maternal outcome and increases the incidence of stunting. Stunting is known as one of the most significant barriers to human development and globally affects around 162 million children under the age of 5 years. The Global stunting incidence in children under 5 years is 149.2 million or about 22.0% of all children under five. The prevalence of stunting in children aged less than 5 years old in Africa is around 31.7%, Southeast Asia is 30.1%, the Eastern Mediterranean Region is 26.2% and in Indonesia it is 24.4%. It is known that children born of women who are less than 20 years have a 1.3 times risk of experiencing stunting and the prevalence of stunting in adolescent pregnant women is around 44.4% compared to mothers who are old enough, namely 35.6%. Purpose: Method: This was a literature review collected from four e-databases search was conducted by PubMed (Medline), Web of science, Scopus and ScienceDirect for articles published between 2019 and 2021 that examine teenage pregnancy and stunting. Existing articles will be filtered and eliminated according to the inclusion criteria and analyzed to find the conclusions from the entire study. Results:. The search led to primary research publications including qualitative and quantitative research. The articles were published between 2019 and 2021. Most of the articles showed that young maternal age influences maternal outcome and we need to pay attention to stunting incidence. Even though there are a lot of factors that play a role in stunting such as nutrition, disease, parent height, etc. but five articles that have been filtered agree that adolescent pregnancy is the main factor that plays a role in stunting.. Conclusion : Our review found the closely related factors that related with stunting are early marriage, clean-healthy behaviors and mental emo-disorder of adolescent mothers. However, there are other factors causing stunting namely direct and indirect factors. Robust programs to support pregnant women and monitor children’s heights from birth will help prevent intergenerational stunting. Nevertheless, it is also necessary to review the policy on how stunting criteria are set in Indonesia based on socio-demographic conditions.